Diversity of moths (lepidoptera : heterocera) in selected localities on selected offshore islands and forest island habitats in Malaysia - Muhamad Ikhwan, Idris (Universiti Malaysia Sarawak (UNIMAS), 2011)
(The diversity and vertical distribution (ground, <2m; canopy > 20 m) of the moths were investigated in tropical forests on offshore islands namely Satang Besar Island, Sarawak and Langkawi Island, Kedah and forest island habitats fragment, Kubah National Park, Sarawak and Perlis State Park, Perlis by using Pennsylvanian light traps with 576 trap-hours of sampling efforts for each sites. A total of 1886 individuals comprising of 380 species and 16 families were recorded from all the sites. The highest moth species diversity was Kubah National Park (a=91.19±2.62, H'=4.65,1/D=53.87), followed by Perlis State Park (a=46.75±2.34, H'=3.88,1/D=27.01), Lubuk Sembilang, Langkawi Island (a=44.35±2.07, H'=4.08,1/D=42.44), and Satang Besar Island (a=33.87±2.09, H'=3.59,1/D=21.7). Geometridae was recorded as the dominant family and species for Kubah National Park and Satang Besar Island whereas Arctiidae for Lubuk Sembilang, Langkawi Island and Perlis State Park. The availability of different habitat types in an area promoting greater species diversity for different moth families to exploit, suggesting island size alone cannot be assumed to be a good predictor for species diversity. The application of taxonomic diversity measures elucidated that sites with high diversity index from species richness and abundance accentuation are not necessarily rich taxonomically. Vertical distribution study greatly enhances the probability of capturing the canopy fliers into collection for better interpretation of species diversity. Six species were identified as ground stratum specialist; Omiza lycoraria (Geometridae), Hypomecis costaria (Geometridae), Amblychia angeronaria (Geometridae), Tasta micaceata (Geometridae), Cyana costifimbria (Arctiidae) and Cyana malayensis (Arctiidae). Seven species were reported as new distributional records from Peninsular Malaysia; Cispia punt fascia (Lymantriidae), Cyclosiella spiralis (Arctiidae),Hypochrosis cryptopyrrhata (Geometridae), Egnasia sundana (Noctuidae), Gracillina prosthenia (Noctuidae), Sartagine ovafricta (Noctuidae) and Gonoglasa camptogramma (Noctuidae).